2022
DOI: 10.1126/science.abm2948
|View full text |Cite
|
Sign up to set email alerts
|

Natural history–guided omics reveals plant defensive chemistry against leafhopper pests

Abstract: Although much is known about plant traits that function in nonhost resistance against pathogens, little is known about nonhost resistance against herbivores, despite its agricultural importance. Empoasca leafhoppers, serious agricultural pests, identify host plants by eavesdropping on unknown outputs of jasmonate (JA)–mediated signaling. Forward- and reverse-genetics lines of a native tobacco plant were screened in native habitats with native herbivores using high-throughput genomic, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 73 publications
0
38
0
Order By: Relevance
“…Bacterial pathogens, pests and viruses reduce overall crop yield by up to 30% (Jones et al, 2016; Huang et al, 2021; Bai et al, 2022). Pst DC3000 causes bacterial speck on tomato and Arabidopsis leaves, and infection lessens tomato quality and retards the growth and development of Arabidopsis (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial pathogens, pests and viruses reduce overall crop yield by up to 30% (Jones et al, 2016; Huang et al, 2021; Bai et al, 2022). Pst DC3000 causes bacterial speck on tomato and Arabidopsis leaves, and infection lessens tomato quality and retards the growth and development of Arabidopsis (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Plants have evolved complex and effective defense mechanisms in response to various pathogen attacks (Jones and Dangl, 2006; Bai et al, 2022). The first layer of plant defense is pathogen‐associated molecular patterns (PAMPs)‐triggered immunity (PTI), most likely via a set of pattern‐recognition receptors (Zhang and Zhou, 2010; Peng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…(2022) reported that JA is a major component in tobacco defending against leafhopper, a sucking insect. 44 Actually, BPH can induce the expression of OsAOS at 6 h after infestation ( Figure 1d ), and LF can also induce the expression of OsPAL1 at 1 h ( Figure 1c ), while we did not find obviously higher SA accumulation in parent plants infested by LF ( Figure 2b ), in addition, silencing of OsAOS and OsCOI1 did not enhance parents’ ( Figure 3b,c ) and ratoons’ resistance to BPH ( Figure 7b,c ); thus, our data indicates a complex interaction between JA and SA signaling during infestation of these two insects with different feeding style, further work using SA deficient mutants will be needed to determine whether the priming resistance against BPH requires SA perception in subsequently generated ratoons.…”
Section: Discussionmentioning
confidence: 99%
“…When released into natural habitats, these forward genetic tools can be used to study the frassomics of multitrophic interactions mediated by PSMs. 64 This journal is © The Royal Society of Chemistry 2022 Nat. Prod.…”
Section: Future Directions For Functional Studies Of Psmsmentioning
confidence: 99%
“…This natural history guided approach can be an enormous boon for forward-genetics guided approaches, as exemplified by the recent discovery of new defense chemistry using this approach. 64 N. attenuata plants in nature interact with more than 30 different herbivore and pathogen taxa, and these can be used to screen large forward-genetic plant populations. Five of these interacting insects are being used as high-throughput screeners to phenotype traits of N. attenuata plants.…”
Section: Introductionmentioning
confidence: 99%